2018
DOI: 10.3390/su10072398
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Emissions on Corporate Financial Performance: Evidence from the South African Firms

Abstract: Abstract:The impact of carbon emissions on corporate financial performance within the African corporate setting has remained open and inconclusive, owing primarily to the unavailability of data. However, this paper examines the effect of carbon emissions (Scope 1, Scope 2, and Scope 1 and 2) on the financial performance (ROE, ROI, and ROS) of 63 South African CDP companies for the 2015 fiscal year. Using multiple regression techniques, the paper found overwhelming evidence of a negative relationship between ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 38 publications
12
64
1
Order By: Relevance
“…Concerning negative outcomes, the future research can shed light on the organizational slowness of the corporate strategy and the country effect. Similarly, it is essential to conduct in-depth investigation to determine the reason behind the variance between the findings of this and an African study (Ganda & Milondzo, 2018) on the relationship between CEP and CFP. It leads to the readers that there may be a difference in the outcome owing to regional differences in the management models, accounting principles, and methods of drafting financial statements, which effect the calculation of financial ratios and the evaluation of the policies and practices adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning negative outcomes, the future research can shed light on the organizational slowness of the corporate strategy and the country effect. Similarly, it is essential to conduct in-depth investigation to determine the reason behind the variance between the findings of this and an African study (Ganda & Milondzo, 2018) on the relationship between CEP and CFP. It leads to the readers that there may be a difference in the outcome owing to regional differences in the management models, accounting principles, and methods of drafting financial statements, which effect the calculation of financial ratios and the evaluation of the policies and practices adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Although eco‐efficiency indicators were employed as a new set of variables, the authors could not find any relationship whatsoever. The environmental aspect was once again used by Dobre, Stanila, and Brad () who employed a panel fixed model to determine whether there was a relationship between environmental, social, and financial performances; Pandey and Kumar () who analyzed the connection between environmental cost and a firm's profit earning ability; Cheon, Maltz, and Dooley () who used the top 10 U.S. ports as their sample; Alexopoulos, Kounetas, and Tzelepis () who analyzed the relationship regarding Greek manufacturing companies; Gatimbu, Ogada, Budambula, and Kariuki () who analyzed the relationship between environmental efficiency and profitability in small‐scale tea processors in Kenya; Ganda and Milondzo () who analyzed the impact of carbon emissions on financial performance; and Shin, Ellinger, Nolan, DeCoster, and Lane () who examined whether employing renewable could have a relationship with firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies worth singling out are the ones by Cubas-Díaz and Martínez Sedano (2018) Goel & Misra, 2017;Paun, 2017;Lucato et al, 2017;Ganda & Milondzo, 2018;Atan et al, 2018;Xiao et al, 2018;Krause, 2018). Ten studies either could not find enough evidence to determine the existence of such relationship (Ching et al, 2017;Lean & Nguyen, 2014;Santis et al, 2016;Siew et al, 2013) or found mixed results when comparing different sectors (Ameer & Othman, 2012;Mervelskemper et al, 2013;Cristófalo et al, 2016;Lassala et al, 2017;Charlo et al, 2015;Chang & Kuo, 2008;.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used five objective criteria to measure the company's performance are as follows [30]: ROA (return on asset), ROE (return on equity), and sales, which are accounting-based criteria; on the other hand, there are also the Tobin q and MV/BV (market value/book value), which are the market-based criteria. For example, Ganda and Milondzo [31] investigated how the intensity of these dimensions of carbon emissions (Scope 1, 2, and 1 and 2) impact corporate financial performance indicators (ROE, ROI, and return on sales-ROS). Ortas et al [19] investigated the influence of organizations' board independence on corporate social performance (CSP), and the results showed that the independence of a company's board positively influences CSP.…”
Section: Financial Performancementioning
confidence: 99%